The Historian's Craft - Bloch, Marc (Brill | Manohar Publishers & Distributors, 2024)
This seminal work by the founder of Annales School, Marc Bloch discusses history writing from many perspectives, rather than a singular method and what comprises history. The Historian's Craft covers the issues concerning what comprises history. This book also deals with the concept of time, historical observation, criticism, analysis, and causation. Citing pieces of evidence from certain history-related documents such as the Commentaries of Julius Caesar and Protocols of the Elders of Zion, he exemplifies the examples of history writing and forgeries. This book explains that the history based on judgemental aspect is something not to be done, and provides a wider explanation rather than providing in normative terms.